Time trends in malaria incidence from 1992 to 2021 in high-risk regions: An age‑period‑cohort analysis based on the Global Burden of Disease study 2021 - Yu Cao; Hao Wu; Yongping Zhang; Xueyi Wu; Jingjing Li; Hanwu Chen; Wei Gao (International Journal of Infectious Diseases)
Objectives: Malaria, caused by plasmodium parasites, remains one of the world's most significant infectious diseases due to its high incidence and mortality. This study aims to analyze malaria incidence globally, identify high-risk regions, and examine long-term trends in incidence to provide important evidence for malaria eradication. Methods: We used data from the Global Burden of Disease Study 2021, applying the age-period-cohort model to estimate the effects of age, period, and cohort on malaria incidence from 1992 to 2021. We calculated the net drift (overall annual percentage change), local drift (annual percentage change for each age group), longitudinal age curves (expected longitudinal age-specific rates), and period (cohort) relative risks. Results: In 2021, the global age-standardized incidence rate of malaria declined to 3485.3 per 100,000 (95% uncertainty interval [UI]: 2804.5-4435.7), a 5.24% decrease since 1992. Sub-Saharan Africa has the highest age-standardized rate at 20,225.9 per 100,000 (95% UI: 16,033.5-25,862.6), accounting for 92% of all new cases globally. From 1992 to 2021, age-standardized malaria incidence rates generally declined across highest-risk regions, although Sub-Saharan Africa saw the smallest decline, with a net drift of –0.74% (95% confidence interval: –1.32 to 0.17). The 0-4 age group faces the highest risk, which decreases with age. Conclusion: Malaria continues to threaten public health in Sub-Saharan Africa, particularly among the 0-4 age group. Efforts should focus on enhancing access to malaria control measures and implementing targeted public health policies for priority groups.